SCANNING ELECTRON MICROSCOPIC STUDY OF MUCUS CELL OPENING IN THE ALIMENTARY CANAL OF HETEROPNEUSTES FOSSILIS (BLOCH) - SWAPNA CHOUDHARY (The Bioscan, 2015)
The detail of goblet cells was identified in the mucosal folds with special attention in the different region of the gut epithelium of Heteropneustes fossilis.Mucus gland openings were visible in between the elevated wrinkled or microridged individual epithelial cells in the roof of buccopharynx and the anterior portion of the oesophagus. The number of these cells is almost the same as much as epithelial cells in an approximately 1:1 ratio. Heavy mucus secretion is observed in the pyloric region of the stomach. Whereas prominent mucus gland opening were not visible in the cardiac region of the stomach. The mucosal membrane of the intestine is characterised by the zigzag folds, with plenty of mucus secretion. The mucus cells opening of the rectum are numerous making reticular appearances with heavy fold of mucus. The number of mucus cell opening in the gut of Heteropneustes fossilis is variable this indicates that the mucus secretion and its function vary in the different region of the alimentary canal. The study gives an idea about the number of mucus cell opening in the different region have their functional importance.